МОНГОЛ ОРНЫ ХӨРСНӨӨС ЯЛГАСАН АКТИНОМИЦЕТИЙН АНГИЛАЛЗҮЙН СУДАЛГААНЫ ДҮНГЭЭС (Proceedings of the Mongolian Academy of Sciences, 2016)
Soil samples were collected from Khentii and Tuv provinces in Mongolia. Two strains (N11, N22) were selected for polyphasic approach which including morphological, physiological and phylogenetic analysis. Phylogenetic analysis revealed that the strain N22 has highest the 16S rRNA similarity of 99.39% with Streptomyces ghanaensis NBRC 15414(T). The 16S rRNA genes sequence of 1418 nucleotides was generated for N11 and compared to the validly described species of genus Streptomyces as closest neighbors. Phylogenetic analysis revealed that the strain N11 has highest the 16S rRNA similarity of 98.51% with Streptomyces yerevanensis NBRC 12517(T). Also some phenotypic characteristics were different from type strains. Preliminary study shows that strain N11 might be new actinomycete species. However, need to determine the genetic distance between two microorganisms by using DNA-DNA hybridization methods.